2014
DOI: 10.1186/1756-0500-7-409
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of depression among older people in Rawalpindi, Pakistan

Abstract: BackgroundDepression is common among elderly in developed countries and it is more pronounced in institutional settings. In Pakistan there is a lack of empirical data on depression among this segment of the population particularly with reference to their living arrangements.The objectives of the present study are to report the magnitude of depression among elderly having two different residential arrangements and to examine the association of depression and its established demographic factors.FindingsData were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
15
3
Order By: Relevance
“…The explanation of determined prevalence of vitamin B 12 deficiency is probably connected with the fact that more than third (35.7%) of study participants were regularly taking vitamins and mineral as dietary supplements thus improved their vitamin B 12 status. This study also revealed extremely high prevalence (70.0%) of depression among study population that is much higher than the determined prevalence of depression among elderly in other studies in which the prevalence rates varies between 10 and 40% (11,(22)(23)(24). A plausible explanation for this extremely high prevalence of depression in the studied population is the impact of recent history and past war events and the overall economic situation in the society, particularly in the Eastern Croatia, while it is known that war and poor economic situation leads to the increase in the prevalence of depression and all its disastrous consequences (25,26).…”
Section: Discussionsupporting
confidence: 45%
“…The explanation of determined prevalence of vitamin B 12 deficiency is probably connected with the fact that more than third (35.7%) of study participants were regularly taking vitamins and mineral as dietary supplements thus improved their vitamin B 12 status. This study also revealed extremely high prevalence (70.0%) of depression among study population that is much higher than the determined prevalence of depression among elderly in other studies in which the prevalence rates varies between 10 and 40% (11,(22)(23)(24). A plausible explanation for this extremely high prevalence of depression in the studied population is the impact of recent history and past war events and the overall economic situation in the society, particularly in the Eastern Croatia, while it is known that war and poor economic situation leads to the increase in the prevalence of depression and all its disastrous consequences (25,26).…”
Section: Discussionsupporting
confidence: 45%
“…Behavioral disorders and psychological symptoms often accompany MCI and were reported to affect its presentation and course. Psychopathology, such as depression, anxiety, or apathy, are frequent in pre-dementia stages, dementia, and also in normal aging; prevalence rates for depression in normal older subjects range between 14.6% and 53% (Wada et al, 2004;Wen et al, 2010;Zivin et al, 2010;Vadla et al, 2013;Qadir et al, 2014), for anxiety between 3.7% and 43% (Bryant et al, 2008;Vadla et al, 2013;Arbus et al, 2014;Katzman et al, 2014), and for apathy between 2% and 75.2% (Adams, 2001;Lyketsos et al, 2002;Onyike et al, 2007). Cognitive impairment in major depression is well documented and is part of depression and its DSM criteria; the deterioration of processing speed and executive, attentional, and amnestic functions are frequent findings (Christensen et al, 1997;Lee R. S. C. et al, 2012;Rock et al, 2014).…”
Section: Psychological Symptoms In MCImentioning
confidence: 99%
“…Another study on older adults in Care Homes in Pakistan found a higher prevalence of depressive symptoms using CES-D (69%). 35 Older adults in care homes may generally be less independent and be in worse physical health, and older adults in Singapore may have more social support than Pakistan. A Singapore study on elderly depression in nursing homes had a lower prevalence of 21% using a Structural Clinical Interview that diagnosed clinical depression, instead of CES-D that assessed depressive symptoms.…”
Section: Summary and Interpretation Of Findingsmentioning
confidence: 99%